Particularly vulnerable tribal groups of Tamil Nadu, India: A sociocultural anthropological review - Balasubramanian Ganesh; Thangarasu Rajakumar; Subhendu Kumar Acharya; Sridharan Vasumathy; Sridharan Sowmya; Harpreet Kaur (Wolters Kluwer Medknow Publications, 2021)
"Adivasi" is the collective term for tribes, an indigenous population, and ethnic minorities of India. In general, tribal populations live in harmony with nature and resources within their habitat and largely reside in segregates in an unpolluted and natural environment away from modern civilization. As per the 2011 census, India contains 705 scheduled tribes (STs) and subtribes and 75 primitive tribal clusters. The ST population of Tamil Nadu, India, was found to be 794,697 and broadly spread in 38 districts constituting 36 tribes, among which 6 tribes were grouped as "particularly vulnerable tribal groups" (PVTGs), namely (1) Todas, (2) Kotas, (3) Kurumbas, (4) Irulas, (5) Paniyas, and (6) Kattunayakas, as the number of population in these tribal communities is either declining or remaining static. The state government is offering lots of benefit schemes for the STs, but they have not reached the tribal groups. Health problems of tribal communities have been profoundly influenced by different factors such as social, cultural, educational, economic, and political practices. The tribal peoples are exceedingly disease prone as they do not have access to basic health-care facilities. Therefore, concerned policymakers should focus on the changing health needs of tribal communities. In this regard, the current review article has been focused on the complete details (language, occupation, worship or deity, subdivisions or other names, etc.) of these six PVTGs and also to concentrate on the kind of problems they face while living in the societies. Therefore, the government and nongovernmental organizations need to find a way to improve their livelihoods and health status.